A concurrent prenatal exercise program increases neonatal and placental weight and shortens labor: The GESTAFIT project - Olga Roldan Reoyo (Scandinavian Journal of Medicine & Science in Sports, 2023)
ObjectiveTo explore the influence of a supervised concurrent exercise-training program during pregnancy on maternal and neonatal birth-related outcomes and type of birth.MethodsOne hundred and fifty-nine Caucasian pregnant women from the GESTAFIT project participated in this quasi-experimental study and were allocated into control [(n = 86), (age 33.1 ± 4.8 years old, BMI 24.8 ± 4.1 kg/m2)] or exercise group [(n = 50) (age 33.1 ± 4.1 years old, BMI: 24.7 ± 4.1 kg/m2)]. The exercise group followed a 60-min 3 days/week concurrent (aerobic and strength) training program from the 17th gestational week until birth. Maternal and neonatal birth-related outcomes (i.e., gestational age at birth, duration of labor, placental and neonatal weight and type of birth) were collected from obstetric medical records. Umbilical arterial and venous blood gas analysis were assessed after birth.ResultsThe exercise group increased average duration of the first stage of labor [between-group differences (B): 80.8 min, 95% confidence interval (CI), 4.18, 157.31, p = 0.03] and decreased duration of the second stage of labor [between-group differences (B): 29.8 min, 95% CI: −55.5, −4.17, p = 0.02] compared to the control group. The exercise group showed greater placental [between-group differences (B): 53.3 g (95% CI: 9.99, 96.7, p = 0.01)] and neonatal [between-group differences (B): 161.8 g (95% CI: 9.81, 313.8, p = 0.033)] weight compared to the control group. No differences between groups were found regarding type of birth (p > 0.05).ConclusionsA concurrent and supervised physical exercise program during pregnancy is safe and could promote better maternal and neonatal birth-related outcomes. More studies are needed to clarify the mechanisms by which physical exercise increases neonatal and placenta weight.